Topical Simvastatin Improves Lesions of Diffuse Normolipemic Plane Xanthoma by Inhibiting Foam Cell Pyroptosis - Zha, Siyuan; Yu, Xia; Wang, Xiaoxiao; Gu, Yan; Tan, Yidong; Lu, Ying; Yao, Zhirong (Frontiers in Immunology, 2022)
Xanthoma pathogenesis is speculated to be associated with oxidized low-density lipoprotein (ox-LDL) deposition, although this remains unclear. Most patients with diffuse plane xanthomas present elevated blood lipid levels, and they benefit from treatment with oral lipid-lowering agents. However, there is no available treatment for diffuse normolipemic plane xanthoma (DNPX). In this study, for the first time, we used a topical simvastatin ointment to treat DNPX in three pediatric patients, and observed favorable results. Immunofluorescence staining showed that the pyroptotic pathway was significantly attenuated after topical simvastatin application on the skin lesions of the patients. As ox-LDL deposition was observed in the lesions, we used ox-LDL to build a foam cell model in vitro. In the ox-LDL-induced foam cell formation, simvastatin consistently inhibited pyroptotic activation and inflammation in the macrophages. Additionally, the overexpression of nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) or 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reductase (HMGCR), the known target of statins, reversed the effects of simvastatin. Moreover, gasdermin D (GSDMD) or HMGCR knockdown inhibited ox-LDL-induced pyroptosis. Furthermore, the immunoprecipitation results confirmed the interaction between NLRP3 and HMGCR, and this interaction was inhibited by simvastatin. In conclusion, we demonstrated that topical application of simvastatin ointment might be a promising treatment for DNPX skin lesions and that this therapeutic effect may be related to pyroptosis inhibition via HMGCR inhibition in foam cells. Moreover, xanthoma pathogenesis might be associated with ox-LDL deposition and inflammation.